T8 spinal cord transection in a 6-year-old child - St Clair, Selvon F; Silverstein, Michael; Lieberman, Isador (Evidence-Based Spine-Care Journal, 2012)
Study design: Case report.Objective: To describe a case of spinal cord transection in a 6-year-old child.Background information: Non-missile injury of the spinal cord is not common and its incidence varies according to the country. In addition, to our knowledge, there are no published reports of spinal cord injury (SCI) from a penetrating nail. Here, we report the case of a child who developed complete SCI because of cord transection by a nail.Methods: A detailed history and physical examination were performed along with careful review of the patient’s medical records. In addition, a review of the literature was conducted to assess the incidence and treatment of similar injuries.Case description: A 6-year-old boy was admitted to the hospital after falling from a tree and landing on a nail. His physical examination revealed an emaciated child with multiple decubitus ulcers, lying on his side in bed. Visible was a well-healed posterior puncture wound at the T8 vertebral level. On neurological examination, the patient had 0/5 muscle strength in his lower extremities, symmetrical areflexia, and hypoesthesia below the T8 level. Plain x-ray of the thoracolumbar spine was normal. Magnetic resonance imaging revealed a transected spinal cord at the T8 vertebra, consistent with his nail puncture wound.Discussion: This report describes an unusual case of a complete SCI in a pediatric patient caused by penetrating trauma from a nail. To our knowledge, this is the first case to report on complete SCI due to trauma from a nail.